Factors Affecting NEPSE Index in Nepal - Ale, Gopal Singh (Dibyajyoti Journal, 2025)
The aim of this study was to investigate how macroeconomic factors affect NEPSE index. In this study, descriptive and causal comparative research design have been used to examine the macroeconomic factors such as money supply, inflation, interest rates, exchange rates, and industrial production and its effect on NEPSE index. In this study, ten years of data from the NEPSE index and economic was used. Data for the study were secondary sources such as NEPSE, SEBON, economic surveys, and national periodicals of the NRB. The analysis of the collected secondary data, spanning from 2014 to 2023. The study utilized, descriptive analysis, correlation analysis, and multiple regression analysis. The findings show that the exchange rate and money supply have a statistically significant impact on the NEPSE Index. Specifically, a decrease in the exchange rate and an increase in money supply are associated with changes in the NEPSE Index, while the effects of inflation, interest rates, and industrial production are not statistically significant in this study. The results suggest that changes in these variables are not reliably associated with the NEPSE Index.